Colonial Settlement in West Bank and Means to resist it - AL-Zaeem, Ibrahim Saqer (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
Abstract The settlement project is considered as the cornerstone of the Zionist Movement. It is one of the pillars of Israel’s establishment of its entity after 1948 and 1967, following which Israel managed to control every part of the occupied lands. This study aims to understand the Zionist ideology, policies and goals, demonstrate the Palestinian and international positions on settlements, and recognize how serious those positions are. The researcher uses the descriptive and historic approaches, and addresses two main topics: The Settlement Projects, its concepts and practices, and the international position on the settlement project and means to resist it. The study also concludes that the Israeli occupation was based on two essentials cornerstones: Immigration and Settlements. After the Jewish immigration was reduced, the settlements became the most important element of the Jewish creed. Settlements are the heart of the Israeli existence; thus, the occupation believes that its presence is bound by the continuation of establishing settlements.